Microcrystals of an organic fluorescent dye grown in the presence of various PAMAM dendrimers: Control of the morphology and optical properties - Franck Bertorelle; Fatima Al-Ali; Suzanne Fery-Forgues (International Journal of Photoenergy)
Microcrystals of a fluorescent dye, 4-n-octylamino-7-nitrobenzoxadiazole, were prepared by the reprecipitation method. Poly(amidoamine)dendrimers bearing anionic, cationic or neutral terminating groups were used as additives in the recrystallization medium. They directed the formation of thin plates or spindlelike microcrystals. The UV/vis absorption and emission properties were investigated on the microcrystal suspensions.